Graded-aperture flexible aerogel heat insulation coating capable of serving for long time in environment of 1100 DEG C
By optimizing the ratio and process, a graded pore size flexible aerogel thermal insulation coating is formed, which solves the problem of high brittleness in high temperature environments, achieves the thermal insulation effect of long-term service in 1100℃ environment, and reduces production costs.
Patent Information
- Application Number
- CN202411613940.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Existing aerogel thermal insulation coatings are highly brittle in high temperature environments, cannot achieve complete deformation, and are costly and difficult to widely use.
The graded pore size flexible aerogel thermal insulation coating is used to optimize the ratio and process, combining components such as aluminum dihydrogen phosphate, water, γ-glycidyl etheroxypropyl trimethoxysilane, α-alumina, emulsifier, defoaming agent, aerogel nanofiber and aerogel powder, to form a structure in which the P-O-Si-Al mesh skeleton and the nanofiber skeleton are intertwined and overlapped by optimizing the ratio and process, and improve the flexibility and constructionability of the coating.
It realizes heat-insulating coatings that are in service for a long time in 1100℃, improves the flexibility and mechanical properties of the coatings, reduces production costs, and is suitable for large-scale production and applications.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation coatings, and in particular relates to a graded pore size flexible aerogel thermal insulation coating capable of serving for a long time in an environment of 1100°C. Background Art
[0002] Traditional thermal insulation and fireproof materials use organic resins as binders, which greatly limits their upper temperature limit. At the same time, they contain organic volatiles and are prone to aging and failure. Aerogel, as a super thermal insulation material, is expensive and often only plays an important role in special engineering environments. With the continuous upgrading of technology, silica aerogel has now achieved industrial mass production, with low cost and quality that can fully meet the needs of construction projects. However, the more commonly used products in current projects are aerogel felt and aerogel composite felt, which have the problems of high brittleness and poor mechanical properties. Summary of the invention
[0003] Based on the above-mentioned deficiencies in the background technology, the purpose of the present invention is to provide a graded pore size flexible aerogel thermal insulation coating that can serve for a long time in an environment of 1100°C, which solves the problems of stable preservation of aerogel molecules in the coating and the brittleness of inorganic coatings that cannot be completely deformed, retains the porous insulation properties of aerogel, and at the same time improves the workability and flexibility of aerogel powder, thereby achieving long-term service in a high temperature environment.
[0004] The technical solution adopted by the present invention is as follows: a graded pore size flexible aerogel thermal insulation coating capable of long-term service in an environment of 1100°C, wherein the components are proportioned as follows by mass: 10 to 30 parts of aluminum dihydrogen phosphate, 10 to 35 parts of water, 10 to 30 parts of γ-glycidyloxypropyltrimethoxysilane, 5 to 17 parts of α-alumina, 1 to 3 parts of emulsifier, 1 to 3 parts of defoamer, 1 to 6 parts of aerogel nanofibers, and 3 to 5 parts of aerogel powder.
[0005] Furthermore, the optimized proportion of each component by mass is as follows: 30 parts of aluminum dihydrogen phosphate, 33 parts of water, 30 parts of γ-glycidyloxypropyltrimethoxysilane, 8 parts of α-alumina, 1 part of emulsifier, 1 part of defoamer, 1 to 3 parts of aerogel nanofibers, and 5 parts of aerogel powder.
[0006] Furthermore, in the aerogel thermal insulation coating as described above, the particle size of the α-alumina is 0.5 microns to 20 microns, the defoamer is tripolyphosphate or silicone defoamer, the emulsifier is hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide or benzalkonium chloride, the aerogel nanofiber is mullite fiber or zirconium silicate fiber, the fiber diameter is 500 nanometers to 1.5 microns, the length distribution is 40 microns to 200 microns, the aerogel powder is hydrophobic silica aerogel or hydrophobic silicon-aluminum aerogel, and the particle size is 1 micron to 20 microns.
[0007] Furthermore, the aerogel thermal insulation coating as described above has micron-sized pores on its surface after curing, and its internal structure is composed of a PO-Si-Al network skeleton and a nanofiber skeleton interpenetrating and overlapping each other, and the tough phase (transformed from a dispersed phase to a continuous phase) and the brittle phase (transformed from a continuous phase to a dispersed phase) undergo phase inversion, thereby achieving improved mechanical properties of the coating.
[0008] Another object of the present invention is to provide a method for preparing the graded pore size flexible aerogel thermal insulation coating capable of long-term service in an environment of 1100° C., the steps being as follows:
[0009] Step 1: Mix aluminum dihydrogen phosphate powder and water according to the formula ratio until completely dissolved, add γ-glycidyloxypropyltrimethoxysilane and emulsifier, shake, and let stand until the bubbles completely disappear to obtain a preliminary coating solution;
[0010] Step 2: adding the aerogel powder to the preliminary coating solution described in step 1 in three portions according to the weight ratio, shaking the aerogel powder each time to make it fully and evenly dispersed, to obtain a coating emulsion, wherein the volume of the added aerogel powder is 1 to 4 times the volume of the preliminary coating solution;
[0011] Step 3: placing the aerogel nanofibers in water, fully shearing and dispersing them, centrifuging the dispersed nanofibers and removing excess water, drying them, and adding them to the coating emulsion described in step 2 according to weight proportions, then adding α-alumina powder, and shaking to obtain a paste-like aerogel coating;
[0012] Step 4: Add the defoamer according to weight proportions to the aerogel paste described in step 3, stir, and let stand for 24 hours to obtain the heat-insulating and fire-retardant aerogel coating.
[0013] Furthermore, in step 1 of the method described above, the oscillation frequency is 100 to 300 rpm, the amplitude is 4 mm, 8 mm, and the oscillation time is 6 to 12 hours.
[0014] Furthermore, in step 2 of the method described above, the oscillation frequency is 300-400 rpm, the amplitude is 20 mm, and the oscillation time is 2 hours.
[0015] Furthermore, in step 3 of the method described above, the shear rate is 3000-8000 r / min, the shear time is 1-5 min, the centrifugal rate is 12000 r / min, the centrifugal time is 20 min, the drying temperature is 105°C, the time is 1 hour, the oscillation frequency is 400 rpm, the amplitude is 20 mm, and the oscillation time is 3 hours.
[0016] Furthermore, the method as described above is characterized in that the stirring rate in step 4 is 300 to 500 r / min and the time is 30 to 60 min.
[0017] Principle of the present invention: the present invention adopts an emulsifier to form emulsion molecules from aerogel powder, so that the pore size of the aerogel can be retained during the preparation process, and at the same time, a defoaming agent that can slowly act with the emulsifier molecules is added to slowly break the emulsion molecules during the coating and curing process, so that the heat insulation effect of the aerogel is completely retained and exerted, and the emulsion slow-release effect allows the coating to retain more micron-level pores during the curing process, thereby realizing the design and implementation of the graded pore size of the coating; at the same time, in view of the problem of high brittleness of the dihydrogen phosphate aluminum coating, the present invention proposes to use a silane coupling agent as a modifier to pre-crosslink the dihydrogen phosphate aluminum solution, and under the action of the curing agent α-alumina, the PO-Al, Si-O-Al, and PO-Si-Al network structures are continuously interwoven, so that the coating can be cured at room temperature, and at the same time, the originally brittle main phase is transformed into a dispersed phase, and the principle of brittle-tough phase inversion is used to realize the high bending deformation ability of the brittle coating.
[0018] Advantages and beneficial effects of the present invention:
[0019] 1. The raw material cost of the present invention is low, the production process is simple, the production energy consumption is low, and large-scale mass production can be easily achieved. It can be widely used in steel structure protection in places such as bridges, airports, and stations, and has broad market prospects.
[0020] 2. The thermal insulation coating of the present invention can be cured at room temperature, and the cured product mainly exists in an amorphous state. At the same time, the flexible ceramic nanofibers form an interpenetrating network structure, transforming the brittle phase from a continuous phase to a dispersed phase, and the tough phase from a dispersed phase to a main phase, which greatly improves the flexibility of the coating, has excellent deformation ability, can bend, twist, etc., and bear more complex loads. Compared with other inorganic coatings, not only the deformation ability is greatly improved, but also the bonding strength is significantly improved, and it has more excellent mechanical properties.
[0021] 3. The thermal insulation coating of the present invention has excellent self-leveling properties, fast surface drying speed, and convenient construction, which greatly shortens the process flow of coating construction. At the same time, the coating thickness can be flexibly controlled to meet the needs of different engineering environments, greatly improving production efficiency.
[0022] 4. The thermal insulation coating of the present invention can be sprayed into a thermal insulation coating with a thickness of 3 mm. When the front side is heated to 1100°C and continuously heated, the back side temperature can be maintained at about 220°C within 30 minutes, thereby achieving thermal insulation and fire prevention, and meeting the engineering requirement that the temperature of the steel structure should be below 300°C for a long time when exposed to fire. This performance is significantly better than other thermal insulation materials such as aerogel felt.
[0023] 5. Compared with the existing aerogel thermal insulation coating, the service temperature of the aerogel coating of the present invention can be increased to 1000-1300°C, and it has excellent low-temperature crack resistance and can adapt to more complex engineering environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The preparation process of the present invention;
[0025] Figure 2 This is a sample picture after the paint is applied;
[0026] Figure 3 This is the back temperature curve result of the 3mm thick coating test;
[0027] Figure 4 This is the bending morphology of 2mm thick coating;
[0028] Figure 5 This is the microstructure diagram of the graded pore size of the coating;
[0029] Figure 6 It is the complete cycle test process of the coating and the microscopic morphology of the test area;
[0030] Figure 7 This is the back temperature curve result of the sample subjected to 10,000 bending cycles. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention. In the present invention, unless otherwise specified in specific circumstances, the numerical range listed herein includes the upper and lower limits, as well as all integers and fractions within the range, and is not limited to the specific values listed when the range is limited.
[0032] Example 1: This example provides a graded pore size flexible aerogel thermal insulation coating capable of long-term service in an environment of 1100°C, the ratio of which is 150g of aluminum dihydrogen phosphate, 300g of water, 100g of γ-glycidyloxypropyltrimethoxysilane, 80g of α-alumina, 10g of benzalkonium chloride, 10g of tripolyphosphate, 10g of mullite aerogel nanofibers, and 51g of silica aerogel powder, with the volume fraction of the solution being 200%.
[0033] The method for preparing the aerogel coating of Example 1 of the present invention comprises the following steps:
[0034] 1) mixing aluminum dihydrogen phosphate powder and water according to the weight proportions until completely dissolved, adding γ-glycidyloxypropyltrimethoxysilane and an emulsifier, oscillating at a frequency of 200 rpm and an amplitude of 4 mm for 6 hours, and standing until bubbles completely disappear to obtain a preliminary coating solution;
[0035] 2) adding the aerogel powder to the preliminary coating solution described in step 1 three times according to the weight proportion, and oscillating at a frequency of 400 rpm and an amplitude of 20 mm for 2 hours after each addition of the aerogel powder to make it fully and evenly dispersed, to obtain a coating emulsion;
[0036] 3) placing the aerogel fibers in water, and using a high-speed shearing machine to shear and disperse them at 5000 r / min for 3 minutes, the diameter of the dispersed fibers is 500 nanometers to 1.5 microns, and the length distribution is 40 microns to 200 microns. The dispersed nanofibers are centrifuged at 12000 r / min for 20 minutes, and the excess water is poured off, and the fibers are dried at 105° C. for 1 hour, and then added to the coating emulsion described in step 2 according to the weight ratio, and then α-alumina powder is added, and the frequency of 400 rpm and the amplitude of 20 mm are oscillated for 3 hours to obtain a paste aerogel coating;
[0037] 4) Add the defoaming agent to the coating emulsion described in step 3 according to weight, stir at a speed of 400 r / min for 30 minutes, and let it stand for 24 hours to obtain a heat-insulating and fire-retardant aerogel coating.
[0038] Example 2: The only difference between Example 2 and Example 1 is that the raw materials and proportions of the aerogel are as follows: the components are composed by mass of 200g of aluminum dihydrogen phosphate, 200g of water, 200g of γ-glycidyloxypropyltrimethoxysilane, 130g of α-alumina, 10g of benzalkonium chloride, 10g of silicone defoamer, 2g of zirconium silicate aerogel nanofibers, and 60g of silica aerogel powder, with the volume fraction of the solution being 300%.
[0039] Example 3: The only difference between Example 3 and Example 1 is that the raw materials and proportions of aerogel are as follows: the components are composed by mass of 300g of aluminum dihydrogen phosphate, 300g of water, 250g of γ-glycidyloxypropyltrimethoxysilane, 170g of α-alumina, 10g of octadecyltrimethylammonium bromide, 10g of tripolyphosphate, 30g of mullite aerogel nanofibers, and 81g of silica-alumina aerogel powder, with the volume fraction of the solution being 400%.
[0040] Example 4: The only difference between Example 4 and Example 1 is that the raw materials and proportions of aerogel are as follows: the components are composed by mass of 300g of aluminum dihydrogen phosphate, 330g of water, 300g of γ-glycidyloxypropyltrimethoxysilane, 80g of α-alumina, 10g of hexadecyltrimethylammonium bromide, 10g of tripolyphosphate, 30g of mullite aerogel nanofibers, and 90g of silica-alumina aerogel powder, which is 300% by volume fraction of the solution.
[0041] Comparative Example 1: An adjustment was made based on Example 1, except that no emulsifier was added, and the aerogel was emulsified by itself to form a Pickering emulsion. The amounts of other raw materials and the preparation method were the same as those in Example 1.
[0042] Comparative Example 2: The only difference between Comparative Example 2 and Example 1 is that the raw materials and proportions of the aerogel are as follows: 300 g of aluminum dihydrogen phosphate, 300 g of water, 100 g of γ-glycidyloxypropyltrimethoxysilane, 80 g of α-alumina, 10 g of benzalkonium chloride, 10 g of tripolyphosphate, and 60 g of silica aerogel powder, with a solution volume fraction of 200%.
[0043] Comparative Example 3: The only difference between Comparative Example 3 and Example 1 is that the raw materials and proportions of the aerogel are as follows: 300 g of aluminum dihydrogen phosphate, 300 g of water, 80 g of α-alumina, 10 g of benzalkonium chloride, 10 g of tripolyphosphate, 30 g of zirconium silicate aerogel nanofibers, and 45 g of silica aerogel powder, which is 200% by volume fraction of the solution.
[0044] Detection test
[0045] Test 1: Examples 1 to 4 and Comparative Examples 1 to 3 were painted with a coating thickness of 2 to 3 mm, and cured at room temperature for 7 days. The construction performance and the surface morphology and cracking after drying and curing were tested. The test results are shown in Table 1.
[0046] Table 1 Curing and cracking of coatings
[0047] category Construction performance Cracking Example 1 Excellent fluidity No cracks Example 2 Good liquidity No cracks Example 3 Poor fluidity, viscous No cracks Example 4 Good liquidity No cracks Comparative Example 1 Unable to construct No cracks Comparative Example 2 Excellent fluidity Cracking Comparative Example 3 Good liquidity Cracking
[0048] The results show that the surfaces of Examples 1 to 4 did not crack after drying and curing. On the one hand, the flexible nanofibers, aluminum phosphate coating skeleton and aerogel powder constituted a stable three-dimensional interpenetrating network structure, which provided good skeleton support for the coating and endowed the coating with greater deformation capacity. On the other hand, γ-glycidyloxypropyltrimethoxysilane was hydrolyzed and reacted in the acidic aluminum dihydrogen phosphate solution to form a more complex network structure of -Al-O-Si- and -Al-(O)P(O)-Si-, and the inorganic polymer chain was further extended. The tough phase was transformed from a dispersed phase to a continuous phase, and the brittle phase was transformed from a continuous phase to a dispersed phase, which improved the overall flexibility and cross-linking degree of the coating and effectively solved the cracking problem of the aerogel coating. The working test results of Examples 1 to 3 and Comparative Examples 1 and 2 show that the fluidity of the coating has a relatively direct relationship with the dosage of aerogel powder. When the dosage of aerogel powder is 400%, the coating cannot self-level after brushing, and the construction is difficult. Without adding an emulsifier, the coating sample in which the aerogel powder self-emulsifies to form a Pickering emulsion presents a non-Newtonian fluid state and cannot be constructed.
[0049] Test 2: The adhesive and thermal insulation properties of the coating were tested by brushing the coating sample of Example 4. The direct shear viscosity of the coating on different substrates such as stainless steel plate, calcium silicate board, PP board, wood board, glass board, and cardboard was tested respectively, and the test results are shown in Table 2. The back surface temperature of the coating sample of Example 4 at different thicknesses during continuous heating for 30 minutes was tested, and the test results are shown in Table 3.
[0050] Table 2 Adhesion strength and damage of coatings
[0051] category Bond strength (MPa) Destruction form Stainless steel plate 13.6 Paint fracture Calcium silicate board 3.7 Base material fracture PP board 0.12 Paint Desorption board 10.8 Substrate interface fracture glass plate 3.9 Base material fracture cardboard 0.27 Substrate interface fracture
[0052] The results show that the bonding strength of the coating sample of Example 4 is related to the type of substrate. For samples that can be wetted or penetrated, the bonding effect is better, and the bonding strength can reach more than 10MPa. For example, the bonding strength of the wood board reaches 10.8MPa, and the failure form is the fracture of the bonding interface, which shows that the adhesion strength of the coating is very high, while the interface is relatively weak, so it is damaged when bearing load. For stainless steel plates, the coating can penetrate into the steel matrix within a certain depth range, the interface is strengthened, and the bonding strength is as high as 13.6MPa. When damaged, the coating itself breaks. For substrates that cannot be wetted, especially hydrophobic PP boards, the bonding only relies on weak intermolecular forces and hydrogen bonds, so it reflects a lower bonding strength. The substrates such as calcium silicate boards and glass boards have low tensile strength themselves, and they break when bearing loads, while the coating does not show obvious changes. Cardboard is made of multiple layers of mixed cellulose overlapped, and the local tensile strength is low, so it is also damaged at the interface between the substrate and the coating when bearing loads. The coating of Example 4 shows unique advantages in the bonding protection of steel structures.
[0053] Table 3 Thermal insulation test results of coatings
[0054]
[0055] The results show that when the front temperature of the coating sample of Example 4 is 1100±20℃, the back temperature decreases with the increase of thickness, and the back temperature is only 210±3℃ when the thickness is 3mm. This is because the emulsion slow-release effect and the aerogel nanopores jointly construct the graded pore structure of the coating. The system presents a porous structure from micron to nanometer, which makes the coating have very excellent thermal insulation performance. It can fully meet the requirement that the back temperature of the steel structure is lower than 300℃ for a long time.
[0056] Test 3: The long-term service performance of the coating was simulated by brushing the coating sample of Example 4. The 2.5 mm coating was subjected to a 90° bending cycle test for 1000, 5000, and 10000 cycles respectively to observe whether cracks were generated. The test results are attached. Figure 6 The samples after 10,000 cycles were tested for thermal insulation performance. The test method was to monitor the back temperature curve of the coating. The test time was 3,600 seconds. The test results are attached. Figure 7 .
[0057] The results show that the coating has no visible cracks after multiple bending cycles. The microscopic morphology of the test area photographed with a scanning electron microscope still shows no obvious cracks. The coating has good complete fatigue performance and no degradation of mechanical properties during simulated long-term service. The samples after the cycle were subjected to a long-term butane burner ablation test. The back temperature curve was monitored and found to be close to the back temperature curve test results of the second test. During the test, the back temperature of the 2.5mm thick coating was maintained at about 250℃, and the thermal insulation performance did not degrade. It is generally speculated that the long-term service performance of the coating is good.
[0058] From the above examples and comparative examples, it can be seen that the present invention provides a graded pore size flexible aerogel thermal insulation coating that can be used for a long time at 1100° C. The entire preparation process has simple process equipment, low raw material cost, high production efficiency, good thermal insulation performance, and is suitable for large-scale production and promotion and application.
[0059] The above description is only a partial embodiment of the present invention and is not intended to limit the present invention. Any equivalent changes and modifications made according to the content of the present invention are within the protection scope of the present invention.
Claims
1. A graded pore size flexible aerogel thermal insulation coating capable of long-term service at 1100°C, characterized in that: The components are proportioned as follows by mass: 10 to 30 parts of aluminum dihydrogen phosphate, 10 to 35 parts of water, 10 to 30 parts of γ-glycidyloxypropyltrimethoxysilane, 5 to 17 parts of α-alumina, 1 to 3 parts of emulsifier, 1 to 3 parts of defoamer, 1 to 6 parts of aerogel nanofibers, and 3 to 5 parts of aerogel powder.
2. According to claim 1, a graded pore size flexible aerogel thermal insulation coating capable of long-term service in an environment of 1100°C, characterized in that: The components are proportioned by mass as follows: 30 parts of aluminum dihydrogen phosphate, 33 parts of water, 30 parts of γ-glycidyloxypropyltrimethoxysilane, 8 parts of α-alumina, 1 part of emulsifier, 1 part of defoamer, 1 to 3 parts of aerogel nanofibers, and 5 parts of aerogel powder.
3. The flexible aerogel thermal insulation coating with graded pore size capable of long-term service at 1100°C according to claim 1 or 2, characterized in that: The particle size of the α-alumina is 0.5 micron to 20 microns, the defoamer is tripolyphosphate or silicone defoamer, the emulsifier is hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide or benzalkonium chloride, the aerogel nanofiber is mullite fiber or zirconium silicate fiber, the fiber diameter is 500 nanometers to 1.5 microns, the length distribution is 40 microns to 200 microns, the aerogel powder is hydrophobic silica aerogel or hydrophobic silicon-aluminum aerogel, and the particle size is 1 micron to 20 microns.
4. The flexible aerogel thermal insulation coating with graded pore size capable of long-term service at 1100°C according to claim 3, characterized in that: After curing, the surface has micron-sized pores, and its internal structure is composed of a PO-Si-Al mesh skeleton and a nanofiber skeleton interpenetrating and overlapping each other.
5. The method for preparing a flexible aerogel thermal insulation coating with graded pore sizes capable of long-term service at 1100°C according to claim 3, characterized in that: Here are the steps: Step 1: Mix aluminum dihydrogen phosphate powder and water according to the formula ratio until completely dissolved, add γ-glycidyloxypropyltrimethoxysilane and emulsifier, shake, and let stand until the bubbles completely disappear to obtain a preliminary coating solution; Step 2: adding the aerogel powder to the preliminary coating solution described in step 1 in three portions according to the weight ratio, shaking the aerogel powder each time to make it fully and evenly dispersed, to obtain a coating emulsion, wherein the volume of the added aerogel powder is 1 to 4 times the volume of the preliminary coating solution; Step 3: placing the aerogel nanofibers in water, fully shearing and dispersing them, centrifuging the dispersed nanofibers and removing excess water, drying them, and adding them to the coating emulsion described in step 2 according to weight proportions, then adding α-alumina powder, and shaking to obtain a paste-like aerogel coating; Step 4: Add the defoamer according to weight proportions to the aerogel paste described in step 3, stir, and let stand for 24 hours to obtain the heat-insulating and fire-retardant aerogel coating.
6. The method for preparing a graded pore size flexible aerogel thermal insulation coating capable of long-term service at 1100° C. according to claim 5, characterized in that: The oscillation frequency in step 1 is 100 to 300 rpm, the amplitude is 4 mm, 8 mm, and the oscillation time is 6 to 12 hours.
7. The method for preparing a graded pore size flexible aerogel thermal insulation coating capable of long-term service at 1100° C. according to claim 5, characterized in that: The oscillation frequency in step 2 is 300-400 rpm, the amplitude is 20 mm, and the oscillation time is 2 hours.
8. The method for preparing a flexible aerogel thermal insulation coating with graded pore sizes capable of long-term service at 1100° C. according to claim 5, characterized in that: The shear rate in step 3 is 3000-8000 r / min, the shear time is 1-5 min, the centrifugal rate is 12000 r / min, the centrifugal time is 20 min, the drying temperature is 105°C, the time is 1 hour, the oscillation frequency is 400 rpm, the amplitude is 20 mm, and the oscillation time is 3 hours.
9. The method for preparing a flexible aerogel thermal insulation coating with graded pore sizes capable of long-term service at 1100° C. according to claim 5, characterized in that: The stirring rate in step 4 is 300-500 r / min, and the time is 30-60 min.
Citation Information
Patent Citations
Heat insulation inorganic coating and preparation method thereof
CN104609825A
Light super-strong aerogel heat insulation coating and preparation method thereof
CN113248950A
Preparation method of phosphate gum-based flame-retardant heat-insulating coating highly ceramic in case of fire
CN115433479A
Aerogel thermal insulation coating and production process thereof
CN115612359A
Inorganic coating as well as preparation method and application thereof
CN115851010A